Perancangan Aplikasi Kasir dengan Metode Prototype: Studi Kasus : UMKM Artasari - Isnaurokhmah Isnaurokhmah; Kusumas Astri Anggraeni; Lailatur Rochmah; Ilham Albana (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
As human habits change due to advances in technology and information, technology is increasingly important in various aspects of life. Companies must keep up with development trends in the globalization era to develop their products and compete with fierce business competition. Artasari UMKM produces a variety of chips located in one of the villages in Purbalingga Regency. This UMKM still conducts sales and marketing traditionally. Bookkeeping and recording of transactions are still done manually, which causes many problems, such as consumers not trusting the results of calculations. A cashier information system is needed to improve operational efficiency and transaction security. It can help with data collection, bookkeeping, and recording transactions as well as creating financial reports as needed. In this research, the prototyping model is used to design a cashier application at UMKM Artasari. It is considered to help overcome this problem. This research is expected to improve the operational efficiency and security of UMKM Artasari transactions and increase consumer confidence in the calculation results. The result of the design is a system display consisting of several pages which include the login page, transaction data, sales reports, help, and prototype proof of transactions to be printed.